THE DEPLETION OF TUNGSTEN IN THE BULK SILICATE EARTH: CONSTRAINTS ON CORE FORMATION - Newsom H.E.; Noll Jr.P.D.; Jaeger W.L.; Maehr S.A.; Beserra T.B.; Sims K.W.W. (My University, 1996)
The depletion of the siderophile element tungsten (W) in the bulk silicate Earth (BSE), due to core formation, provides clues to the formation and early evolution of the Earth. This study significantly improves our knowledge of the abundance of W in the continental crust, an important reservoir for W in the BSE. Tungsten is a highly incompatible element, whose absolute concentrations are variable due to igneous processes. Therefore, the abundance of W is normalized to the highly incompatible lithophile element Th, to correct for igneous fractionation since the end of core formation. Similar W/Th ratios are observed in several terrestrial reservoirs, including the depleted mantle (nodules and Mid-Ocean Ridge Basalts), the old continental crust (upper continental sediments and Archean granulites), and the young continental crust (continental and oceanic arcs). The use of Th as a normalizing element is inappropriate, however, in the case of granulite xenoliths from the lowermost continental crust. These samples have higher W/Th ratios due to loss of Th (and U) compared to other incompatible elements including Ba and W. The few komatiite samples investigated have high ratios of W to the normalizing elements, possibly due to loss of the normalizing elements during alteration.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей